The power of AI personalization: Mediated moderation in social & e-commerce - Wenny Candra Mandagie; Robert Kristaung (Jurnal Manajemen dan Pemasaran Jasa, 2025)
This study investigates the impact of AI-driven personalization on key customer outcomes within Indonesia's e-commerce landscape. It examines how personalization influences customer engagement, trust, perceived relevance, customer experience, and purchase frequency. While prior studies have extensively explored AI personalization, limited research has examined its mediated moderation effects on customer behavior in emerging e-commerce markets, particularly in Indonesia. This study addresses the gap by analyzing the moderating effect of education level and the mediating role of perceived relevance in shaping purchase frequency. Using a purposive sampling, data were collected from 251 e-commerce users through structured surveys. The data were analyzed using PLS-SEM. The findings reveal that AI-driven personalization significantly enhances customer engagement, trust, perceived relevance, and customer experience. Additionally, perceived relevance mediates the relationship between personalization and purchase frequency, emphasizing its role in driving consumer behavior. The education level moderates the relationship between customer experience and purchase frequency, suggesting that personalization strategies should be tailored to different educational backgrounds. It contributes to the AI personalization literature by uncovering its moderated mediation effects in social and e-commerce contexts, particularly in emerging markets. Practically, these insights can guide e-commerce practitioners in leveraging AI-driven personalization to enhance customer engagement, trust, and satisfaction, leading to increased purchase frequency. This study has limitations, including potential measurement biases in customer trust and experience, and excluding other influencing factors such as price sensitivity or brand loyalty. Future research should explore additional moderators and mediators, investigate AI personalization across various industries, and examine longitudinal effects to strengthen the findings.